2008
DOI: 10.1111/j.1099-1123.2008.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committees and Voluntary External Auditor Involvement in UK Interim Reporting

Abstract: The study investigates the relationship between audit committee characteristics and the decision to engage external auditors to review published interim reports. The motivation for the study derives from the consensus notion that the audit committee enhances the quality of financial reporting. Using interim reports of 258 UK listed companies published in the period 2001–2002, the results of logistic regression analyses show that the likelihood of engaging an external auditor to review interim reports increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 49 publications
(203 reference statements)
8
57
0
2
Order By: Relevance
“…Jensen and Meckling (1978) in particular suggested that firms may mainly focus on "relevant stakeholders." Arguably, to the extent that various firm-level decisions are greatly influenced by the characteristics of the CEO (Hambrick & Mason, 1984;Sterling, 2014), shareholders (Haniffa & Cooke, 2002;Mangena & Tauringana, 2008), and the board (Forker, 1992;Tricker, 1984), these will influence the choice of relevant stakeholders when firms are making disclosure-related decisions. For example, in continental Europe where countries have a two-tier board structure, a stakeholder may be relevant to the extent that they are represented on the supervisory board.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Jensen and Meckling (1978) in particular suggested that firms may mainly focus on "relevant stakeholders." Arguably, to the extent that various firm-level decisions are greatly influenced by the characteristics of the CEO (Hambrick & Mason, 1984;Sterling, 2014), shareholders (Haniffa & Cooke, 2002;Mangena & Tauringana, 2008), and the board (Forker, 1992;Tricker, 1984), these will influence the choice of relevant stakeholders when firms are making disclosure-related decisions. For example, in continental Europe where countries have a two-tier board structure, a stakeholder may be relevant to the extent that they are represented on the supervisory board.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, foreign investors who are far from firms may demand higher levels of CG disclosures that protect shareholder interests (Bokpin & Isshaq, 2009;Haniffa & Cooke, 2002;Mangena & Tauringana, 2008;Singhvi, 1968). First, chief executive officer (CEO), ownership, and board characteristics may influence firms to be shareholder focused or consider other nonshareholding stakeholders when making CG disclosure decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Temuan ini sejalan dengan penelitian Zhang et al, (2007) yang menemukan bahwa frekuensi rapat komite audit mempengaruhi kualitas pelaporan keuangan dan ada korelasi positif antara kedua variable tersebut. Penelitian lain melaporkan bahwa anggota komite audit yang sering melakukan rapat yang terjadwal memiliki lebih banyak waktu untuk melakukan peran pengawasan dalam pelaporan keuangan dibandingkan dengan anggota komite audit yang jarang melakukan rapat secara teratur (Chen et al, 2005;Collier & Gregory, 1999;Hoque et al, 2013;Karamanou & Vafeas, 2005;Mangena & Tauringana, 2008;Munro & Buckby, 2008). Singkatnya, elemen integrated reporting dalam annual report akan meningkat bila komite audit aktif melakukan pertemuan rutin dan terjadwal.…”
Section: Hasil Dan Pembahasanunclassified
“…(Chen, Moroney, & Houghton, 2005;Collier & Gregory, 1999;Hoque et al, 2013;Karamanou & Vafeas, 2005;Mangena & Tauringana, 2008;Munro & Buckby, 2008). Anggota komite Audit yang bertemu secara teratur sering diharapkan dapat melakukan tugas-tugas pemantauan lebih efektif daripada ang jarang melakukan pertemuan rutin.…”
unclassified
“…This might be reassuring to those who, mindful of the agency problems of the modern corporation (Jensen and Meckling, 1976), view audit committees as having an important monitoring, supervisory or conformance role to play (see Spira and Bender, 2004). However, in the case of a minority of companies, not all audit committee members were independent according to the terms of the Code, which entails the risk that their objectivity and effectiveness in monitoring could be undermined, to the detriment of performance (see Chan and Li, 2008;Mangena and Tauringana, 2008). In some cases this appeared to be a temporary or transitional stage, but there was also evidence that some companies disagreed with the Code, particularly in relation to length of "association".…”
Section: Discussionmentioning
confidence: 99%